2009
DOI: 10.1002/jor.21019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of muscle load on tibiofemoral knee kinematics

Abstract: A comparative kinematics study was conducted on six cadaver limbs, comparing tibiofemoral kinematics in five conditions: unloaded, under a constant 130 N ankle load with a variable quadriceps load, with and without a simultaneous constant 50 N medial and lateral hamstrings load. Kinematics were described as translation of the projected centers of the medial (MFT) and lateral femoral condyles (LFT) in the horizontal plane of the tibia, and tibial axial rotation (TR) as a function of flexion angle. In passive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
106
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(130 citation statements)
references
References 47 publications
17
106
2
2
Order By: Relevance
“…experimental tests performed in a previous in-vitro analysis on cadaver legs (Innocenti et al, 2009a,b;Victor et al, 2009bVictor et al, , 2010.…”
Section: Analyzed Motor Taskmentioning
confidence: 98%
See 1 more Smart Citation
“…experimental tests performed in a previous in-vitro analysis on cadaver legs (Innocenti et al, 2009a,b;Victor et al, 2009bVictor et al, , 2010.…”
Section: Analyzed Motor Taskmentioning
confidence: 98%
“…The loaded squat was reproduced numerically, simulating an existing knee kinematics rig (Maletsky, 1999;Victor et al, 2009cVictor et al, , 2010 in terms of geometries, constraints, inputs and outputs. The simulated machine and its function and constraints are shown in Fig.…”
Section: Numerical Model Of the Replaced Kneementioning
confidence: 99%
“…Another difference with the OKR is that the UGKR not only controls the quadriceps force but also the hamstring forces. The latter have shown a considerable contribution to the knee kinematics [32].…”
Section: A System Descriptionmentioning
confidence: 99%
“…A combination of both is often applied within the same simulator [22], [32], [33]. The Purdue knee simulator [22] is controlling five axes in order to impose squat motions, where the actuators can be controlled in either position or force mode.…”
Section: Introductionmentioning
confidence: 99%
“…Victor et al 14) reported that the tibia was rotated more laterally with a 50-N lateral hamstring load than with a 50-N medial hamstring load in knee flexion experiments using cadavers. The medial hamstrings (semitendinosus and semimembranosus muscles) are inserted at the pes anserine tendon at the proximal anteromedial tibia (semitendinosus) and posterior surface of the medial condyle of the tibia (semimembranosus) 15) .…”
Section: Introductionmentioning
confidence: 99%